Amazonian lower cretaceous north tocantins state (Brazil) dinosaur track site: conservation significance - Tavares, Lanuze Fabielly S. (2014)
On the left bank of the Tocantins River, near São Domingos, State of Tocantins, northern Brazil, there are at least six vertebrate trackways from the Barremian Corda Formation (Parnaíba Basin) first reported by Leonardi (BuenosAires 1:215–222, 1980) and assigned to iguanodontid dinosaurs. Later, these trackways were reassigned as belonging to sauropods. Until 2011, this locality was subject to river floods during seasonal rain cycles. Since then, the amount of water on the flatstones was substantially modified due the implantation of the “Usina Hidroeletrica de Estreito”, which has a dam 160 km upstream from the trackways locality. Recent fieldwork in the area has revealed that only a part of four original trackways is still preserved. The specimens, with poor to moderate preservation, are represented by large semicircular pes imprints lacking digital impressions mostly overlapping the hand print, which supports a sauropodian origin. Here, the authors consider and suggest geotourism as an important tool to protect and preserve the São Domingos’ footprints.